A Short History of the Cooperative Movement in Northern Malabar, Kerala - 2024; Thuppilikkat, Ashique Ali (Economic and Political Weekly, 2024)
Despite the pervasive presence of cooperatives in Kerala's society, scholarly accounts of the cooperative movement's history are limited. Synthesising archival and field research conducted in northern Malabar between 2018 and 2022, this history is traced. The contributions of social reform movements, social service organisations, and anti-feudal and anti-colonial movements to Kerala's cooperative movement are explored. The paper highlights the sociopolitical history of the cooperative movement and its ties to oppressed caste communities and labour resistance.
Keywords: Anti-Colonial; Anti-Feudal; Kerala's Society; Movements; Northern Malabar; Cooperative Movement